Rekonstruksi Tujuan Pendidikan Islam: Studi Komparasi Pemikiran Majid Irsan al-Kilani dan Ahmad Dahlan - Ramadhan, Ossi Marga (Program Pascasarjana Universitas Ibrahimy, 2020)
The process of education always goes through dynamic stages. It always adapts to the atmosphere of the students' conditions and current development. Therefore the reconstruction of Islamic education’s purpose is very important. Especially during the era of al-Kilani and Ahmad Dahlan, both of them met their respective concerns so that they thought to modify and to change Islamic education’s purpose. This article aims to find the standpoint of their version of Islamic education’s purpose. It was library research that referred to the sources of related literature and was processed using comparative descriptive analysis. The finding showed that there were similarities between them, such as first, the similarity in the setting of purpose formulation. Second, there were also similarities in the basic foundation for their educational purpose which are Al-Qur'an and Al-Hadith. However, there were a few differences from their standpoint such as in aspects of educational background and intellectual heritage.